Documenting heritage language experience using questionnaires - Tomić, Aleksandra; Rodina, Yulia; Bayram, Fatih; De Cat, Cécile (Frontiers in Psychology, 2023)
There exists a great degree of variability in the documentation of multilingual experience across different instruments. The present paper contributes to the "methods turn" and individual differences focus in (heritage) bilingualism by proposing a comprehensive online questionnaire building on existing questionnaires and the experience of using them to document heritage bilingualism: the Heritage Language Experience (HeLEx) online questionnaire. We validate HeLEx against an extended version of the Language and Social Background Questionnaire designed for heritage speakers (HSs), LSBQ-H, by comparing data elicited with both questionnaires in turn from a group of Turkish HSs (n=174, mean age=32). Our validation focuses on traditional language background variables, including language exposure and use, language proficiency, language dominance, as well as a more novel measure of language entropy. The analyses are based on a subset of key questions from each questionnaire that capture language experience for up to five languages, four modalities, and five social contexts. In a subsequent set of analyses, we explore the impact of different types of response scales, response mechanisms, and manners of variable derivation on the informativity of the data they can provide, in terms of the scope, granularity and distributional properties of the derived measures. Our results show that both HeLEx and LSBQ-H are successful at detecting the important distributional patterns in the data and reveal a number of advantages of HeLEx. In the discussion, we consider the impact of methodological choices regarding question phrasing, visual format, response options, and response mechanisms. We emphasize that these choices are not trivial and can affect the derived measures and subsequent analyses on the impact of individual differences on language processing and outcomes.